The association of bullous pemphigoid with cerebrovascular disease and dementia: a case-control study. - Taghipour, K; Chi, C; Vincent, A; Groves, R; Venning, V; Wojnarowska, F (2010)
OBJECTIVE: To investigate the relationship between bullous pemphigoid (BP) and neurologic disease. DESIGN: Case-control study. SETTING: Tertiary care center for immunobullous diseases and skin tumor clinics at a university hospital in Oxford, England. PARTICIPANTS: Ninety consecutive patients with BP and 141 controls. MAIN OUTCOME MEASURES: Age-adjusted prevalence of neurologic disease in patients and controls. Time interval between the diagnosis of neurologic disease and BP and type of associated neurologic disease. RESULTS: At least 1 neurologic diagnosis was present in 42 patients (46%) compared with 16 controls (11%). Patients had significantly increased odds for neurologic diseases regardless of age and sex (crude odds ratio [OR], 6.8; 95% confidence interval [CI], 3.5-13.3; adjusted OR, 6.2; 95% CI, 3.1-12.4). Four major neurologic diagnoses were observed (cerebrovascular disease, dementia, Parkinson disease, and epilepsy), with statistical significance for cerebrovascular disease and dementia (crude OR for cerebrovascular disease, 6.3; 95% CI, 2.8-14.2; adjusted OR, 6.0; 95% CI, 2.6-13.6; crude OR for dementia, 10.7; 95% CI, 2.3-49.0; adjusted OR, 7.9; 95% CI, 1.7-37.3). When accurate data on time of onset of neurologic disease were present (36 of 42 patients [85%]), BP followed neurologic disease in most patients (26 of 36 patients [72%]), with a median interval of 5.5 years. CONCLUSION: Bullous pemphigoid is significantly associated with cerebrovascular disease and dementia.